2020
DOI: 10.3389/fnut.2020.574725
|View full text |Cite
|
Sign up to set email alerts
|

Cow's Milk and Dairy Consumption: Is There Now Consensus for Cardiometabolic Health?

Abstract: Cow's milk and dairy products derived from this complex food source have long been proposed as beneficial to human health, yet underlying clinical evidence of direct benefit continues to raise controversy. Limited evidence supports positive cardiometabolic effects of a number of dairy macro- and micronutrient components including whey protein and casein, unsaturated fats, milk fat globule membrane (MFGM) and polar phospholipids, vitamin D and calcium, in addition to non-bovine components including bacterial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 174 publications
(265 reference statements)
0
28
0
2
Order By: Relevance
“…More pertinently, a body of data supports a negative association between milk intake and the risk of developing dysglycaemia, dyslipidaemia, and hypertension [1,4]. However, with gold-standard data from long-term randomised controlled trials (RCTs) featuring type II diabetes (T2D) and cardiovascular disease (CVD) incidence as primary endpoints not currently available, the causality of these findings remains to be confirmed [5]. Nonetheless, putative explanations for a possible metabolic syndrome risk reduction include a direct modulation of the glycaemic response [2,6], and an indirect modulation of body weight through upregulation of postprandial thermogenesis [6][7][8] and/or suppression of appetite [9][10][11].…”
Section: Cow Milk Consumption and Cardiometabolic Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…More pertinently, a body of data supports a negative association between milk intake and the risk of developing dysglycaemia, dyslipidaemia, and hypertension [1,4]. However, with gold-standard data from long-term randomised controlled trials (RCTs) featuring type II diabetes (T2D) and cardiovascular disease (CVD) incidence as primary endpoints not currently available, the causality of these findings remains to be confirmed [5]. Nonetheless, putative explanations for a possible metabolic syndrome risk reduction include a direct modulation of the glycaemic response [2,6], and an indirect modulation of body weight through upregulation of postprandial thermogenesis [6][7][8] and/or suppression of appetite [9][10][11].…”
Section: Cow Milk Consumption and Cardiometabolic Healthmentioning
confidence: 99%
“…However, with the current knowledge coming from trials of limited sample size and inconsistent study design, this verdict cannot yet be determined to be conclusive and remains largely controversial. Indeed, the need for longer-term RCTs evaluating the effect of CLA isomers on incidence of T2D and CVD is emphasised [5].…”
Section: Body Weight and Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“… 84 Such guidance arises in part from evidence originating from the Seven Countries Study and similar investigations 85 , 86 that supports recommendations to limit total fat and saturated fat to < 30% and < 10% of total dietary energy, respectively. 87 , 88 These recommendations, especially those related to saturated-fat consumption, are the subject of much debate 89 and are inconsistent with findings of observational studies suggesting that all-cause mortality, CVD, stroke, and T2DM are unrelated to saturated-fat intake. 90 Others also have reported that dietary saturated fat increases circulating low-density lipoprotein cholesterol (LDL-C) but noted that the increase often corresponds with an increase in large LDL particles that have a weaker relationship to CVD risk than do small LDL particles that have greater atherogenicity.…”
Section: Controversy Surrounding the Consumption Of Dairy And Dairy Fat On Cardiometabolic Healthmentioning
confidence: 99%